Extracellular CIRP (eCIRP) and inflammation - Aziz, Monowar; Brenner, Max; Wang, Ping (Journal of leukocyte biology, 2019)
Cold‐inducible RNA‐binding protein (CIRP) was discovered 2 decades ago while studying the mechanism of cold stress adaptation in mammals. Since then, the role of intracellular CIRP (iCIRP) as a stress‐response protein has been extensively studied. Recently, extracellular CIRP (eCIRP) was discovered to also have an important role, acting as a damage‐associated molecular pattern, raising critical implications for the pathobiology of inflammatory diseases. During hemorrhagic shock and sepsis, inflammation triggers the translocation of CIRP from the nucleus to the cytosol and its release to the extracellular space. eCIRP then induces inflammatory responses in macrophages, neutrophils, lymphocytes, and dendritic cells. eCIRP also induces endoplasmic reticulum stress and pyroptosis in endothelial cells by activating the NF‐κB and inflammasome pathways, and necroptosis in macrophages via mitochondrial DNA damage. eCIRP works through the TLR4‐MD2 receptors. Studies with CIRP−/− mice reveal protection against inflammation, implicating eCIRP to be a novel drug target. Anti‐CIRP Ab or CIRP‐derived small peptide may have effective therapeutic potentials in sepsis, acute lung injury, and organ ischemia/reperfusion injuries. The current review focuses on the pathobiology of eCIRP by emphasizing on signal transduction machineries, leading to discovering novel therapeutic interventions targeting eCIRP in various inflammatory diseases. Review on the pathobiology, signal transduction and novel therapeutic strategies involving eCIRP in inflammatory diseases.